STRATEGIC PLANNING AND FIRM PERFORMANCE: A SYNTHESIS OF MORE THAN TWO DECADES OF RESEARCH. - MILLER, C. C.; CARDINAL, L. B. (Academy of Management Journal, 1994)
Building on previous contingency frameworks, we developed an encompassing contingency model that might explain the inconsistent planning-performance findings reported in previous research. The model was empirically tested using meta-analytic data drawn from 26 previously published studies. Results suggest that strategic planning positively influences firm performance and that methods factors are primarily responsible for the inconsistencies reported in the literature. The substantive contingency factors that we examined, some of which have been frequently cited as important by previous researchers, did not have a large impact.